Good Faith Principle Of Contract Law For The Islamic Banking System - KHAN, M.; HAN, N. H; CHOI, S. B; BAE, J. H (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The Islamic banking system has attracted the attention of scholars, practitioners, and investors. In the Islamic banking system, the good faith principle may not adequately serve the purpose for which the Islamic banks were set up. This paper is to examine both the present debate and the current practice of the good faith principle of Islamic contract law in banking system. The study uses secondary data procured from published research papers, the Holy Quran, and the Prophetic Sunnah, which embody all tenets of Islamic law. From our findings, the Islamic banking system is more economically efficient. RESUMEN El sistema bancario islámico ha atraído la atención de académicos, profesionales e inversores. En el sistema bancario islámico, el principio de buena fe puede no cumplir adecuadamente el propósito para el cual se crearon los bancos islámicos. Este documento es para examinar tanto el debate actual como la práctica actual del principio de buena fe del derecho contractual del sistema bancario islámico. El estudio utiliza datos secundarios obtenidos de trabajos de investigación publicados, el Sagrado Corán y la Sunnah profética, que incorporan todos los principios de la ley islámica. Según nuestros hallazgos, el sistema bancario islámico es más eficiente económicamente.